Constructional changes in Brazilian Portuguese in the 20th century: two cases of linguistic deletion - Silva, Augusto Soares da (2024)
This chapter analyzes two constructional changes by deletion of linguistic elements in Brazilian Portuguese (BP) in the 20th century, namely, the null clitic se constructions (specifically, reflexive, reciprocal, middle, anticausative, passive, and impersonal constructions) and the chopping relative construction, as two relevant manifestations of the recent standardization of the BP variety diverging from European Portuguese (EP). Based on a usage-feature and profile-based analysis and adopting a sociocognitive view of language, especially Cognitive Grammar, this study shows that the deletion of the clitic se conveys a shift to a nonenergetic, absolute construal of the event, and that the deletion of the preposition correlates with the grammaticalization of the relative pronoun que and highlights the accessibility of the nominal antecedent. Three contributions to research on language change are stressed: changes by deletion generate new constructions with their own meanings; synchronic constructional alternation, such as the one existing in BP between overt and null se constructions and the one already nonexistent in BP but existing in EP between pied-piping and chopping constructions, allows simulation of the diachronic constructional change in real time; and successful media from the mid-20th century onward, such as TV Globo for the huge Brazilian population, play a central role in language change and standardization.